Investigation of Problem-Solving and Problem-Posing Abilities of Seventh-Grade Students - Arikan, Elif Esra; Unal, Hasan (EDAM, 2015)
This study aims to examine the effect of multiple problem-solving skills on the problem-posing abilities of gifted and non-gifted students and to assess whether the possession of such skills can predict giftedness or affect problem-posing abilities. Participants' metaphorical images of problem posing were also explored. Participants were 20 gifted and 85 non-gifted seventh graders, and quantitative and qualitative research methods were used for data collection and analysis. The relationship between multiple problem-solving skills and giftedness was investigated, and a strong corre lation between problem solving in multiple ways and problem-posing abilities was observed in both the gifted and non-gifted students. Moreover, problem solving in multiple ways was observed in both the gifted and non-gifted students. Metaphorical images were based on the participants' experiences with problem posing, and they associated their positive or negative metaphors depending on their problem-posing performance.
Keywords: Problem solving in multiple ways; Problem posing; Seventh-grade students; Metaphor; TEACHERS; Education & Educational Research